PRODUÇÃO E CARACTERIZAÇÃO DE NANOCÁPSULAS CONTENDO DITELURETO DE DIFENILA E AVALIAÇÃO DA TOXICIDADE EM CAMUNDONGOS - Silva, Fernanda D'Avila da (2015)
Organic tellurium compounds have potential antioxidant effect, it presents as an alternative therapy for the treatment of diseases associated with oxidative stress, but are extremely toxic to rodents. In order to avoid the side effects, especially toxicity, increasing efficacy in the target cell there is the use of nanocarriers. Therefore, the aim of this study was to produce, characterize nanocapsules containing diphenyl ditelluride [(PhTe)2] and evaluate the toxicity in mice. The production of nanocapsules containing (PhTe)2 was performed according to the interfacial deposition of the preformed polymer. After the preparation process, physicochemical characterization was performed. Results demonstrate that the nanocapsules containing (PhTe)2 presented a mean particle size of 256 ± 19 nm, 255 ± 13 nm and 255 ± 22 nm in 24 hours, 7 and 30 days respectively. Regarding the polydispersity index values were 0.15 ± 0.02; 0.13 ± 0.02 and 0.17 ± 0.03 at 24 hours, 7 and 30 days respectively. The zeta potential was -10.7 ± 0.6 mV; -12 ± 0.3 mV and -9.7 ± 1.6 mV in 24 hours, 7 and 30 days respectively. The pH of suspensions were approximately 6 in all analysis times. To evaluate the toxicity, swiss male adult mice treated intraperitoneally at doses of 5 mg / kg and 25 mg / kg were evaluated for clinical signs and symptoms, weight gain, consumption of water and food, organ weights, behavioral open field test and biochemical measurements: oxaloacetic transaminase, pyruvic transaminase, urea, creatinine and cholesterol. Atrophy of the forelegs observed for the higher dose of both the free compound and as nanoencapsulado consequent change in locomotion and exploratory activity in the animals treated with the nanocápsulas containing (PhTe)2 were the results for evaluation of clinical signs and symptoms, it was observed in the same way weight loss of the animals. With regards to biochemical measurements, animals treated with the nanocapsules (PhTe)2 showed elevation of oxalacetic transaminase activity in a dose of 5 mg / kg and cholesterol for the two doses. Thus, the results evidence that animals treated with the nanocapsules (PhTe)2 showed toxicological effects in a short period of time when compared to the free compound, suggestive of active vectorization effectively.